Pengaruh Kualitas Pelayanan, Harga dan Kepercayaan Produk terhadap Keputusan Pembelian pada PT Laris Manis Utama Cabang Bali - Sudewa, I Gusti Ngurah Rangga; Ayu Wimba, I Gusti; Suartina, I Wayan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The population in this study were 272 members at the main PT Laris Manis Bali branch. The number of samples in this study was 160 people who were determined using a purposive sampling technique and tested using multiple linear regression analysis techniques. The results of this research indicate that service quality has a positive effect on purchasing decisions. Price has a positive effect on purchasing decisions. Product trust has a positive influence on purchasing decisions, suggested by PT. Laris Manis Utama Bali Branch to continue to improve service quality, adjust prices and level of product trust so that purchasing decisions increase. PT Laris Manis is advised to continue to improve service quality standards, maintain price availability in line with product quality, and strengthen consumer confidence to support increased purchasing decisions. This suggestion is based on research results which show that respondents want fast service and a neat appearance, prices that reflect product quality, and trust in the products offered. In future research, it is recommended to investigate other variables such as consumer behavior, brand awareness, and brand ambassadorship.